Representasi fungsional aditif ortogonal pada ruang fungsi terintegral denjoy umum= Representation of orthogonally additive functional on the space of general Denjoy integrable functions - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
INTISARI Chew Tuan Seng ( 1985 ) berhasil menyusun representasi dua jenis fungsional. fungsional linear dan fungsional aditif ortogonal. pada ruang fungsi terintegral Henstock. Dalam makalah ini ditelaah penyusunan representasi fungsional pada ruang fungsi terintegral Denjoy Umum. khususnya fungsional aditif ortogonal, dan representasi ini merupakan salan satu generalisasi representasi fungsional . pada ruang fungsi terintegral Henstock tersebut. ABSTRACT Chew Tuan Seng (1985) wrote representations of functionals defined on the space of Henstock integrable functions. This paper describes how to find representations of functionals defined on the space of General Denjoy integrable functions, especially for additive orthogonally functionals. This representation can be considered as a generalization of ones on the space of Henstock integrable functions. Keywords: mekanika gelombang, sistem koordinat kurvalinear ortogonal